Design and fabrication of nano-engineered electrospun filter media with cellulose nanocrystal for toluene adsorption from indoor air - Buyukada-Kesici, Esra; Gezmis-Yavuz, Elifnur; Aydin, Dila; Cansoy, C. Elif; Alp, Kadir; Koseoglu-Imer, Derya Y. (Elsevier BV, 2021)
Abstract The cellulose nanocrystal (CNC)-polyamide 6 (PA-6) composite nanofiber filters were fabricated and examined their structural and mechanical properties and toluene adsorption performances. The effect of polymer concentration (13 wt% and 17 wt%) and CNC ratio (0, 1.0 wt%, 1.5 wt%, and 2.0 wt%) on the characteristics and adsorption abilities of nanofiber filters were investigated. The nanofiber filter including 17 wt% PA-6 and 1.5 wt% CNC has shown the best toluene adsorption efficiency of 50% and improved mechanical properties. As a result, the nanofiber filter having CNC are effective, accessible and cost-saving materials and has been a good candidate as the toluene vapor capture media and it has nearly same removal efficiency like the conventional adsorbents with powder or particle forms. The resultant filters had excellent three-dimensional (3D) fiber structure having micro/nanopores and they can be used in potential applications such as catalyst supports, indoor air filter and respiration masks.